2021
DOI: 10.3390/biology10030181
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating H3 Histone in Response to Repeated Bouts of Exercise Does Not Associate with Parallel Alterations of Cell-Free DNA

Abstract: Numerous studies have shown that cf nDNA significantly rises in stress caused by exercise. However, during nuclear decondensation, released DNA is followed by histones. Histones are also a common disease marker. After PAD4 mediated hypercitrullination extracellular H3Cit exhibits high toxicity contributing to tissue damage which, in cases of systemic inflammation, may lead to multiorgan failure and finally to death. We tested whether circulating histones rise in response to strenuous exercise. Eleven average-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
(78 reference statements)
1
6
0
Order By: Relevance
“…In our previous studies, an exhaustive treadmill run executed according to the same protocol caused an increase in plasma cf n-DNA and citrullinated H3 histone in healthy average trained men and in those with type 1 diabetes [ 7 , 34 , 43 ]. These two biomolecules belong to the markers of neutrophil extracellular traps (NETs) formation [ 44 , 45 ], and it is believed that NETs formation is involved in the immune-metabolic response to strenuous exercise [ 6 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, an exhaustive treadmill run executed according to the same protocol caused an increase in plasma cf n-DNA and citrullinated H3 histone in healthy average trained men and in those with type 1 diabetes [ 7 , 34 , 43 ]. These two biomolecules belong to the markers of neutrophil extracellular traps (NETs) formation [ 44 , 45 ], and it is believed that NETs formation is involved in the immune-metabolic response to strenuous exercise [ 6 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these cells undergo degranulation, which results in increased levels of granular enzymes (e.g., myeloperoxidase) in circulating blood and post-exercise urine [ 3 , 5 ]. Relatively recently, it was found that a certain subset of neutrophils forms neutrophil extracellular traps (NETs) under the influence of exercise with subsequent increase in circulating cell-free nuclear DNA (cf-nDNA), antibacterial granular enzymes and cell-free citrullinated H3 histone [ 6 , 7 ]. Formation of NETs is accompanied by increased ROS production, which seems to be an essential mediator of this process [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic changes after exercise are also stated in histone modifications. PA is found to moderate enzymes responsible for histone acetylation/deacetylation, circulating free citrullinated histones and histone acetylation levels [ 151 , 152 ]. Circulating histones are cytotoxic and may trigger an inflammatory response through TLRs [ 151 ].…”
Section: Epigenetic Changes Involved In Immune Responsesmentioning
confidence: 99%
“…PA is found to moderate enzymes responsible for histone acetylation/deacetylation, circulating free citrullinated histones and histone acetylation levels [ 151 , 152 ]. Circulating histones are cytotoxic and may trigger an inflammatory response through TLRs [ 151 ]. Extensive aerobic training causes the release of H3 histone into the bloodstream.…”
Section: Epigenetic Changes Involved In Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation